Biological significance of Ascorbic Acid (Vitamin C) in human health – a review - Iqbal, Khalid; Khan, Alam; Khattak, Muhammad Muzaffar Ali Khan (Asian Network for Scientific Information, 2004)
The recognition of vitamin C (Ascorbic acid) is associated with history of an unrelenting search for the cause of the ancient hemorrhagic disease scurvy. Isolated in 1928, vitamin C is essential for the development and maintenance of connective tissues. It plays an important role in bone formation, wound healing and the maintenance of healthy gums. Vitamin C plays an important role in a number of metabolic functions including the activation of the B vitamin, folic acid, the conversion of cholesterol to bile acids and the conversion of the amino acid, tryptophan, to the neurotransmitter, serotonin. It is an antioxidant that protects body from free radicals’ damages. It is used as therapeutic agent in many diseases and disorders. Vitamin C protects the immune system, reduces the severity of allergic reactions and helps fight off infections.